Meshfree simulation of flow around airfoil using different turbulent models. (2017) - Wang, Yuanding; Cai, Xiaowei; Ma, Xinjian; Tan, Junjie; Liu, Don; Ren, Dengfeng
The moving least square meshfree method is used to solve the Reynolds-averaged Navier-Stokes equations with two different turbulence models: the renormalisation group (RNG) k-ε model and the Wilcox k-ω model. The moving least square approach with clouds-of-points reconstruction, which can provide results from highly anisotropic clouds of points, is adopted to approximate the spatial derivatives. Both the subsonic and transonic viscous flows around RAE2822 airfoil are simulated. The pressure coefficients of the airfoil surface are calculated, the Mach number contours of the flow fields are presented, and the mean velocity profiles of the boundary layer at different locations are investigated. Some unsteady viscous flow simulation results are also presented. The simulation results show a good agreement with the experiment results and other numerical simulation results. Overall, the simulation results demonstrate that the proposed meshfree numerical algorithm is accurate and capable of modelling turbulence flows around airfoils.